Menyelasaikan Masalah Kehidupan Sehari-hari dalam Konsep Barisan dan Deret Aritmatika - Omega Megarani; Nurintan Maghfirah; Rora Rizky Wandini (Tarbiatuna: Journal of Islamic Education Studies, 2024)
This research aims to solve everyday life problems using the concept of arithmetic sequences and series. The type of research used is qualitative research. The type of data used is secondary data. Data collection method uses library research. The method for this study uses previous literature studies, books and journals. An arithmetic sequence is a number that has a certain pattern and a fixed difference. while an arithmetic series is the sum of all the numbers in the arithmetic series. The concept of arithmetic sequences and series can be applied in life as a solution to solve everyday life problems.